Caso de estudio: análisis y diagnóstico de una empresa del sector agroindustrial peruano, propuesta de un plan estratégico - Cueto Castañeda, Alejandra Lucia (2019)
This work was carried out with the objective of analyzing and proposing a strategic plan for the development and growth of the Camposol company within the agribusiness market. In recent years, agribusiness has been the sector with the greatest expansion and growth both outside and within the Peruvian market for almost 60 products including fruits and vegetables such as blueberries, avocados, mangoes, bananas, grapes, among others. This is due to several reasons: GDP growth in the sector, formal employment possibilities, growth and good performance of agricultural exports in the international market such as the US. UU and China the accessible price of raw materials and the evolution of inflation which has been decreasing. Today the market is moving rapidly and companies seek to differentiate their products through creativity, quality and price. That is why lately we seek to have a brand strategy so the final consumer can recognize and know how to differentiate a product against the variety of the competition.